2021
DOI: 10.3389/fmed.2021.657067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sacubitril-Valsartan in Heart Failure With Preserved Ejection Fraction in Patients Undergoing Peritoneal Dialysis

Abstract: Aims: The effect of the angiotensin receptor–neprilysin inhibitor (ARNI) sacubitril-valsartan in patients with heart failure with preserved ejection fraction (HFpEF) remains unclear, and data on ARNI treatment in peritoneal dialysis (PD) patients are lacking. The present study was designed to assess the efficacy and safety of sacubitril-valsartan in patients with HFpEF undergoing peritoneal dialysis.Methods and Results: End-stage kidney disease (ESKD) patients undergoing PD for 3 months with New York Heart Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 34 publications
1
24
0
1
Order By: Relevance
“…None of the PD patients showed adverse drug reactions such as hypotension, hyperkalaemia, or angioedema (Table 3). These data were similar to those reported by Tang et al (8), but seemed to be lower than those reported in HF population (Table 3) (6).…”
Section: Safety Of Sacubitril-valsartansupporting
confidence: 91%
See 3 more Smart Citations
“…None of the PD patients showed adverse drug reactions such as hypotension, hyperkalaemia, or angioedema (Table 3). These data were similar to those reported by Tang et al (8), but seemed to be lower than those reported in HF population (Table 3) (6).…”
Section: Safety Of Sacubitril-valsartansupporting
confidence: 91%
“…Extra fluid removal of ARNI might contribute to cardiac function protection in PD population. At present, more studies have proved the role of sacubitrilvalsartan on cardiac function (6)(7)(8)(9), which might be the potential mechanism for better PUF. However, obvious improvement of cardiac function could be generally detected 1-3 months or even longer after ARNI application (41,42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A clinical study conducted in hemodialysis patients in China showed that, when ARNI 100 mg BID was used to treat hemodialysis patients with HFrEF or heart failure with midrange ejection fraction, the maximum blood concentration of LBQ657 was within the safe drug concentration range, and ARNI effectively improved their left ventricular ejection fraction (P < 0.05) (75). Another retrospective study including 23 patients also confirmed that ARNI could improve the left ventricular ejection fraction and myocardial marker levels in dialysis patients with HFrEF (76). A Chinese study including 21 peritoneal dialysis patients with HFpEF confirmed that ARNI could also significantly improve the symptoms and signs of heart failure and reduce the levels of heart failure markers, while also exhibiting a tendency to improve cardiac function (77).…”
Section: Arni In Patients With Ckd Undergoing Maintenance Dialysis (H...mentioning
confidence: 83%